Impact of tumor size by clinical N subclassification and histology in trimodality-treated N2 non-small cell lung cancer - Junghee Lee; Jin Lee; Yun Soo Hong; Genehee Lee; Jiyoun Park; Yeong Jeong Jeon; Seong-Yong Park; Jong Ho Cho; Yong Soo Choi; Jhingook Kim; Young Mog Shim; Eliseo Guallar; et al. (Scientific Reports)
Abstract The evolving TNM classification has emphasized the tumor size’s role in NSCLC prognosis, reclassifying stage IIIA patients from the previous edition as stage IIIB (T3-4N2M0, 8th edition). However, the prognostic implications of tumor size and survival in stage III NSCLC patients undergoing neoadjuvant therapy remain unexplored. Therefore, we investigated the association between tumor size and mortality in N2 non-small cell lung cancer (NSCLC) patients undergoing neoadjuvant concurrent chemoradiotherapy followed by surgery (trimodality therapy), considering the number of metastatic N2 stations and histology. We analyzed 756 patients with stage III (T1-3N2) NSCLC who underwent trimodality therapy, excluding those with T3 tumors with invasion components or additional nodules (2003–2019). Overall survival was compared using the Cox-proportional hazards model, while the tumor size-survival relationship was estimated using restricted cubic splines. Using 8th TNM edition, 32.1%, 48.5%, and 19.3% were clinical T1, T2, and T3. During a median follow-up of 53.5 months, 398 patients died. The adjusted hazard ratios for overall survival comparing T2 and T3 to T1 were 1.46 (95% confidence interval, 1.14–1.85) and 1.48 (1.10–1.99). For the extent of clinical N2, large tumor size increased the mortality risk in patients with N2b but not in N2a. Tumor size did not increase mortality risk in squamous cell carcinoma patients; however, the mortality risk was increased with larger tumors in adenocarcinoma. These findings raise the importance of considering tumor size in treatment planning and suggesting tailored strategies.